Long-Term Change in Characteristics of Cloud Vertical Structures Over Sumatra from Radiosonde Observations - Lismalini, Lismalini; Marzuki, Marzuki; Shafii, Mohammad Ali (Jurnal Ilmu Fisika, 2021)
Study on the vertical structure of cloud in Indonesia in terms of climate change is still very limited. We investigated the long-term change in characteristics of cloud vertical structures over Sumatra from three radiosonde observation stations in this work. The cloud base height (CBH), cloud top height (CT), and the number of cloud layers were retrieved using relative humidity (RH) profiles from radiosonde observation. The height of the cloud base is determined by taking the height of the layer with relative humidity (RH) value > 84% with at least a 3% jump in the RH from the ground level. Sumatra’s most frequently observed cloud layer is a one-layer cloud with an average occurrence rate of > 60%, which is slightly larger than the one-layer cloud globally. The percentage of appearance values at the Padang station, Pangkal Pinang, and Medan are 63.58%, 69.50% and 66.05%. The appearance of low-level clouds also dominates in Sumatra compared to other cloud types. CT and CBH increase with the number of years including all seasons. This is in line with the increase in temperature in Indonesia reported by previous researchers. On the other hand, the clouds’ thickness, especially for the cloud with one layer, varies from one location to another. The thickness of clouds decreases at Padang station and does not change at Pangkal Pinang and Medan stations.